Inverted papilloma of the ureter: study of a rare case with emphasis on clinicopathologic implications - Mertziotis, Nikolaos; Kozyrakis, Diomidis; Petrolekas, Andreas; Terzi, Maria; Kapranos, Nikiforos (Canadian Urological Association Journal, 2012)
A 62-year old male patient presented complaining of intermittent macroscopic hematuria. The ultrasonographic investigation revealed a hydronephrosis of remarkable degree with indiscreterenal parenchyma. The abdominal computed tomography scan identified a ureteral lesion with proximal dilatation, hydronephrosis and a functionless ipsilateral renal unit. The retrograde urography showed a 4-cm lesion with multiple filling defects and a smooth contour. The endoscopic examination showed an exophytic lesion, highly suspicious for malignancy. Urine cytology revealed atypia. Right nephroureterectomy was performed and the pathology revealed a ureteral inverted papilloma (UIP). Polymerase chain reaction examination for the presence of human papilloma virus, using GP5+/6+ consensus primers, was negative. The presence UIP should be considered in patients with urotheleal lesions in the ureter when the diagnostic workup for malignancy is inconclusive. The clinical course of the disease seems to be favorable.